IMPROVING LEARNING OUTCOMES ON THE CONCEPT OF SUBSTANCE FORMS AND THEIR CHANGES THROUGH THE 'FRIENDLY AND HEALTHY SOAP' EXPERIMENTAL METHOD AND ROLE PLAYING METHOD: EXPERIMENTAL STUDY ON ELEMENTARY SCHOOL STUDENTS - Yasinia, Amira Riski; Rahmawati, Ika Dian; Wulandari, Rika (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
This study was motivated by the low interest and involvement of students in learning Natural Science in elementary schools, which was caused by ineffective learning methods and difficulties in understanding abstract concepts. This study aims to identify the effect of the "Friendly and Healthy Soap" experimental method and the role-playing method on learning outcomes of material changes in the state of matter in grade IV students. Through an experimental design, this research divided students into two groups: the first group used an experimental approach, while the second group applied a role-playing approach. Hypothesis testing was carried out using the Wilcoxon test and the Mann-Whitney U test with the help of SPSS 27. The results of the Wilcoxon test for both approaches showed significance at the 0.05 level with Asymp.Sig (2-tailed) of 0.000, which indicates that both approaches have a significant influence on student learning outcomes. The Mann-Whitney U test produces an Asymp.Sig (2-tailed) value of 0.003 < 0.05, so that Ho is rejected and Hi is accepted, indicating that there are differences in learning outcomes between the two groups. The average post-test score for the "Friendly and Healthy Soap" experimental approach reached 83.68, higher than the role-playing approach which had an average of 71.57, indicating that the experimental approach was more effective in increasing students' understanding.